Characterization of protein kinase C and its role in catecholamine secretion from bovine adrenal-medullary cells. - Brocklehurst, K W (1985)
Protein kinase C activity towards exogenous histone was detected in a cytosolic fraction of bovine adrenal medulla. The enzyme was dependent on Ca2+ and phosphatidylserine for its activity, with half-maximal activation being achieved at approx. 18 microM free Ca2+ and 8 micrograms of phosphatidylserine/ml. Both diolein and 4 beta-phorbol 12-myristate 13-acetate (TPA) decreased the Ca2+ requirement of the enzyme, half-maximal activation being obtained at approx. 12 microM and 9 microM free Ca2+ respectively in the presence of these agents. Many endogenous proteins in the adrenal-medullary cytosolic fraction were detected whose phosphorylation was dependent on the presence of both Ca2+ and phosphatidylserine. TPA stimulated catecholamine release from cultured bovine adrenal-chromaffin cells in a Ca2+-dependent manner. A23187 also stimulated catecholamine secretion, and at sub-optimal concentrations of TPA and A23187 a synergistic secretory response was obtained. These results are consistent with protein kinase C having a regulatory role in exocytosis in bovine adrenal chromaffin cells.